TINJAUAN YURIDIS TERHADAP HAK PEKERJA LEPAS DI PIZZA HUT S. PARMAN SAMARINDA DALAM PERSPEKTIF HUKUM POSITIF - Putri Febriani (Journal of Law ( Jurnal Ilmu Hukum ), 2022)
ABSTRACTPolicies in the field of manpower in the national development program are always endeavored to create as many job opportunities as possible in various fields. The working relationship between workers and employers themselves must be based on an agreement so that the rights and obligations of each party can be guaranteed. At this time many companies use freelance workers to support the company's business. The problem in this study is the implementation of the agreement and protection of the rights of freelancers using a work agreement for a certain time, in which workers' rights are limited, there is no balance between the rights and obligations of freelancers according to Law Number 13 of 2003 concerning Manpower. The research objective is to analyze the rights of freelance workers in Indonesian positive law. This type of research is normative juridical which is library research and uses a statutory and conceptual approach. Through literature study researchers collect documents and data to be processed using content analysis methods. The results of the study concluded that the impact of intense business competition stemming from global economic developments made companies change their business management structure by reducing management control, one of which was by implementing the practice of using freelance workers for companies to reduce production costs. With the management of the use of freelance workers that has been going on, it does not guarantee the labor rights they should get, especially in terms of remuneration carried out by certain companies. Legal protection for casual workers in Indonesia is regulated in Law Number 13 of 2003 concerning Manpower. One of the reasons for the birth of Law Number 13 of 2003 concerning Manpower is that several laws and regulations that have been in effect so far place workers in a disadvantageous position in the workforce placement service and industrial relations system which highlight differences in position and interests so that they are seen as having no longer in accordance with the needs of the present and the demands of the future. As well as obtaining the right to obtain equal opportunities and treatment without discrimination. Keywords: Freelance Workforc, Law Enforcement, Legal Protection, Positive Law.